Single-nucleus RNA sequencing: Immature excitatory neurons and transformed glia build human BRAFV600E-negative gangliogliomas - Cases-Cunillera, Silvia; Müller, Philipp; Van Waardenberg, Ashley J.; Schoch, Susanne; Huberfeld, Gilles; Höllig, Anke; Delev, Daniel; Hamed, Motaz; Becker, Albert J.; Van Loo, Karen M.J. (Brain Communications, 2025)
Gangliogliomas are glioneuronal neoplasms, generally with a benign evolution, accounting for the most common tumours in patients with long-term pharmacoresistant epilepsy. BRAFV600E has been detected in a high percentage of World Health Organization grade 1 gangliogliomas. However, biopsy collections from epilepsy patients include tumours that meet neuropathological ganglioglioma criteria but lack the BRAFV600E mutation. The molecular pathology of such BRAFV600E-negative gangliogliomas remains largely unexplored. We here focused on decoding the molecular and cellular profiles of these BRAFV600E-negative gangliogliomas at the single-cell resolution. Our results identify an exclusive profile in excitatory, but not inhibitory, neurons, astrocytes and oligodendrocytes in BRAFV600E-negative gangliogliomas. Moreover, we confirm the presence of immature excitatory neurons with higher expression of genes related to glutamatergic transmission as well as metabolically active astro- and oligodendrocytes which may contribute to epileptogenicity. Our study provides important resources to understand the molecular profile of BRAFV600E-negative gangliogliomas aiming to drive forward future research directions to novel and tailored treatment options for epilepsy.
CRIS-Team Scopus Importer:2025-10-24
Keywords: glutamatergic; immature excitatory neurons; neuronal development